Pengaruh Konflik Dan Kecerdasan Emosional Serta Etos Kerja Terhadap Produktivitas Kerja Pegawai Pada Kantor Inspektorat Kabupaten Kutai Kartanegara - Rezza Scantya Ramadhan; Ardi Paminto; Sri Wahyuni (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
This study aims to describe objectively about the effects of conflict, Emotional Intelligence And The work ethic on Productivity Employees At Work Inspectorate Office of Regency. The total population used 104 Civil Servant (PNS) In the Inspectorate Office Kutai district, with a census of the sampling technique. Analysis of data using multiple linear regression. Hypothesis testing Using F test and t test, and data processing using the SPSS program.The results showed that variable = X1, Kcerdasan Emotional / EQ = X2, and X3 = influential work ethic together on the productivity of Employee Work on office Inspektort Kutai regency = Y.Top Influential Variables emotional artifice Dominant castes against Productivity employees working in the inspectorate offices Kutai regencyKeywords : Conflict, Emotional intelligence, Work Ethics and Productivity.